Progressive resistance training to prevent arm lymphedema in the first year after breast cancer surgery: Results of a randomized controlled trial. Issue 10 (11th January 2019) - Ammitzbøll, Gunn; Johansen, Christoffer; Lanng, Charlotte; Andersen, Elisabeth Wreford; Kroman, Niels; Zerahn, Bo; Hyldegaard, Ole; Wittenkamp, Merete Celano; Dalton, Susanne Oksbjerg
Abstract : Background: Existing research suggests that progressive resistance training (PRT) after breast cancer (BC) surgery is safe, but the preventive effect on arm lymphedema has yet to be determined. Methods: Women aged 18 to 75 years who were undergoing BC surgery with axillary lymph node dissection were eligible for the study. Recruited on the day of surgery, participants were allocated to intervention or usual care by computer randomization. The intervention consisted of PRT 3 times per week: in the first 20 weeks as a supervised group exercise and in the last 30 weeks as a self‐administered exercise. The primary outcome was arm lymphedema, which was defined as a >3% increase in the interlimb volume difference by water displacement. Measurements were made at the baseline and at a 12‐month follow‐up by physiotherapists blinded to group allocation. Analyses of effects included t tests and regression models; missing data were addressed by multiple imputation. Results: Among the 158 randomized women, no mean group difference was found in arm volume (0.3%; 95% confidence interval, –1.7% to 2.3%) or lymphedema incidence (adjusted odds ratio, 1.2; 95% confidence interval, 0.5‐2.8). None of the participants exited the program because of adverse events. Conclusions: This study provides no evidence that PRT can prevent arm lymphedema in the first year after BC, but the results corroborate the importance and safety of resistance training for patients, including women at high risk for lymphedema. Abstract : This randomized controlled trial shows no evidence that progressive resistance training can prevent arm lymphedema in the first year after breast cancer. However, the results corroborate the importance and safety of resistance training in rehabilitation for patients, including women at high risk for lymphedema.